2020
DOI: 10.1038/s41433-020-01256-5
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and visual outcomes of small incision lenticule extraction (SMILE) in eyes with thin corneas

Abstract: Objectives To report the refractive and visual outcomes of small incision lenticule extraction (SMILE) with the thinnest corneal thickness (CCT) of less than 500 µm and evaluate it in terms of safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…At the same time, at 24 months follow up, higher rates of HOA were reported. It should also be noted that a corneal thickness of < 475 μm is among the contraindications for SMILE surgery [ 17 ]. Ganesh et al (2015) published an efficacy and safety study of SMILE combined with collagen crosslinking in patients with thin corneas (mean central corneal thickness of 501.3 ± 25.9 μm) and borderline corneal topography ( n = 40 eyes).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, at 24 months follow up, higher rates of HOA were reported. It should also be noted that a corneal thickness of < 475 μm is among the contraindications for SMILE surgery [ 17 ]. Ganesh et al (2015) published an efficacy and safety study of SMILE combined with collagen crosslinking in patients with thin corneas (mean central corneal thickness of 501.3 ± 25.9 μm) and borderline corneal topography ( n = 40 eyes).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study between SMILE and LASIK revealed that approximately 90%-95% of patients achieved uncorrected distance visual acuity of 20/20 within the initial day following SMILE surgery [ 21 ]. SMILE's visual recovery process is notably swifter than LASIK [ 21 ]. Studies examining SMILE in patients with thin corneas have demonstrated its safety and efficacy in treating myopia, yielding satisfactory outcomes [ 21 , 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…SMILE's visual recovery process is notably swifter than LASIK [ 21 ]. Studies examining SMILE in patients with thin corneas have demonstrated its safety and efficacy in treating myopia, yielding satisfactory outcomes [ 21 , 22 ]. However, visual outcomes in individuals with thin corneas may lag slightly behind those with average corneal thickness [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…There was no difference between the 1, 3, and 6mo results in the right and left eyes (P=0.15, P=0.16, respectively). DISCUSSION Since SMILE was first announced, it has opened a new horizon of refractive surgery [6,[15][16][17] . It is known that the visual acuity results are comparable to those of conventional surgery, but there have been studies showing that astigmatism and highorder aberration results are inferior [18][19] .…”
Section: Measuring Cyclotorsion In Smilementioning
confidence: 99%